The Development of Executive Function: Toward More Optimal Coordination of Control With Age. (24th August 2015) - Chevalier, Nicolas
Abstract: Emerging executive function, which allows children to control their thoughts and actions, predicts success in life. A key challenge for children is to engage control in a way that matches ever‐changing demands of tasks. In addition to engagement of more control resources and more mature control strategies, developing executive function also requires that children coordinate available control strategies more flexibly as they age. More optimal coordination of control (or meta‐control) ensures dynamic adjustment of control engagement to match more effectively moment‐to‐moment variations in the demands of tasks and results in more economic cognitive functioning.